2013
DOI: 10.1080/0267257x.2013.766627
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive age and grocery-store patronage by elderly shoppers

Abstract: This paper discusses and evaluates the impact of cognitive (or self-perceived) age on grocery store patronage by elderly shoppers. Cognitive age is seen to be a more accurate reflection of changes related to age and aging than chronological age. Based on self-concept theory, the authors propose that cognitive age moderates the effects of perceptions of store attributes on satisfaction with a store. The hypotheses tests used a sample of 404 supermarket patrons aged 60 and above. The latent construct, cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 58 publications
(121 reference statements)
1
32
0
Order By: Relevance
“…The procurement of food is a fundamental task that must be carried out by most people and can be considered a cumbersome task that must be performed frequently [30]. Senior shoppers are exposed to the shopping task for longer periods of time than younger shoppers due to declining fitness and agility, and/or simply due to having more disposable time [29]. Consumers who have ambulation and dexterity problems, as do many of the shoppers in the senior demographic, find this chore especially challenging [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The procurement of food is a fundamental task that must be carried out by most people and can be considered a cumbersome task that must be performed frequently [30]. Senior shoppers are exposed to the shopping task for longer periods of time than younger shoppers due to declining fitness and agility, and/or simply due to having more disposable time [29]. Consumers who have ambulation and dexterity problems, as do many of the shoppers in the senior demographic, find this chore especially challenging [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in a sample of French seniors, Guiot (2001) found an average difference of 11.97 years. In a recent study of elderly Western Europeans, Teller et al (2013) found an average age difference of 10.83 years, while in an Australian sample of seniors, Cleaver and Muller (2002) found an average difference of 10.2 years. Even when studying a broad cross section of consumers in different chronological 507 Available Online at: http://grdspublishing.org/ age categories, average differences between the two age-oriented constructs are typically larger, with most respondents reporting cognitive ages in the range of 3 to 5 years below chronological age (Barak et al, 2011).…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 99%
“…Given the widespread tendency for consumers to disregard their true ages in favor of their own self-perceptions, it becomes apparent that one's self-perceived age may be a better predictor of age-related psychological states, attitudes, or behavioral tendencies than chronological age (Iyer and Reisenwitz, 2010;Moschis and Mathur, 2006;Teller, Gittenberger and Schnedlitz, 2013). In fact, Guido, Amatulli, and Peluso (2014) conclude that one's self-perceived age can affect decision processes even more than one's real age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some retailers have started to target this group of customers because it is growing; its members want the products to be adjusted to the specific needs and they Innovative Positioning as a Marketing Tool of Retailers on the Food Market | 83 are ready to pay for that. Thus, the retailers are interested in searching this market and developing retail patronage (Oates et al, 1996;Teller et al, 2013).…”
Section: Literature Overviewmentioning
confidence: 99%